Zbrodnie cesarza Fokasa - Leszka, Mirosław J. (Acta Universitatis Lodziensis. Folia Historica, 2000)
This article is devoted to accusations towards emperor Phocas which can be found in Byzantine sources and in professional literature. For the Byzantines Phocas became an archetype of a ruler-tyrant. Phocas was accused of exceptional cruelty. Evidence of it was murder of emperor Maurice and his family, extermination of senatorial class or bloody repressions towards circus factions. Contemporary scholars accused Phocas of total incompetence which was a cause of anarchy and Byzantium’s political and economic collapse. Author of the article thinks that such an opinion about Phocas’reign in the light of latest researches is incorrect. Phocas’ cruelty was caused by political reasons most often, and did not occur as anything exceptional in the history of Byzantium. Opinions, about repressions towards senatorial circles and members of circus factions in the light of discerning analise of sources, seem to be exaggerated. Weakness of Byzantine external position was not connected with incompetence of Phocas but with lasting from 608 sanguinary domestic war against Heraelius rather. The legend of evil, blood thirsty Phocas, is the consequence of state of the sources. Sources which were closest to reign of Phocas were written during Heraelius reign. We must remember, that Heraelius was a usurper. Historians who wrote in his time wanted to excuse Heraelius and that is why they slandered Phocas.